Serum galactomannan index for early prediction of mortality in immunocompromised children with invasive pulmonary aspergillosis - Han, Seung Beom (BMC Infect Dis, 2015)
BACKGROUND: Invasive pulmonary aspergillosis (IPA) is the most common invasive fungal disease in immunocompromised patients, and it has a 30 % mortality rate despite appropriate antifungal therapy. This retrospective study was performed to determine risk factors for mortality in immunocompromised children with IPA. METHODS: Medical records of 45 probable/proven IPA cases diagnosed in children with hematologic/oncologic diseases were reviewed. Selected cases were divided into the survival (n = 30) and fatality (n = 15) groups based on survival at 12 weeks after antifungal therapy. Clinical characteristics and serum galactomannan indices (GMIs) were compared between the two groups. RESULTS: Significantly more children in the fatality group were male (p = 0.044), not in complete remission of the underlying malignancies (p = 0.016), and had received re-induction/salvage or palliative chemotherapy (p = 0.035) than those in the survival group. However, none of these factors was significantly associated with mortality in a multivariate analysis. Serum GMIs were higher in the fatality group than in the survival group during the entire period of antifungal therapy, and serum GMI at 1 week after antifungal therapy was most significantly associated with mortality. A serum GMI > 1.50 at 1 week after antifungal therapy exhibited a sensitivity and specificity of 61.5 % and 89.3 %, respectively, in predicting mortality within 12 weeks after antifungal therapy. CONCLUSIONS: Higher serum GMI in the early phase of antifungal therapy was associated with mortality in immunocompromised children with IPA. These children should receive more intensive care for IPA than others.